Does the sars-cov-2 spike protein receptor binding domain interact effectively with the dpp4 (Cd26) receptor? A molecular docking study - Cameron, Kirsten; Rozano, Lina; Falasca, Marco; Mancera, Ricardo (MDPI, 2021)
ACE2 has been established as the main receptor for SARS-CoV-2. Since other human coronaviruses are known to use co-receptors for viral cell entry, it has been suggested that DPP4 (CD26) could be a potential additional binding target or co-receptor, supported by early molecular docking simulation studies. However, recent biophysical studies have shown this interaction to be very weak. We have conducted detailed molecular docking simulations to predict the potential binding interactions between the receptor binding domain (RBD) of the spike protein of SARS-CoV-2 and DPP4 and compare them with the interactions observed in the experimentally determined structure of the complex of MERS-CoV with DPP4. Whilst the overall binding mode of the RBD of SARS-CoV-2 to DPP4 is predicted to be similar to that observed in the MERS-CoV-DPP4 complex, including a number of equivalent interactions, important differences in the amino acid sequences of SARS-CoV-2 and MERS-CoV result in substantially weakened interactions with DPP4. This is shown to arise from differences in the predicted proximity, nature and secondary structure at the binding interface on the RBD of SARS-CoV-2. These findings do not support DPP4 being a significant receptor for SARS-CoV-2.